The Effects of Student Composition on Teacher Turnover: Evidence from an Admission Reform - Krzysztof Karbownik (Institute of Labor Economics (IZA), 2020)
This paper examines the effects of student ability on teacher turnover using data from Stockholm high schools and an admission reform that led to the exogenous reshuffling of pupils. The results indicate that a 10-percentile-point increase in student credentials decreases the probability of a job separation by up to 10 percentage points. These effects vary somewhat across different groups of teachers and are found mainly for mobility between schools rather than out of the profession. Teachers react most strongly to direct measures of student ability, grades from compulsory school, rather than to other correlated characteristics such as immigrant origin or parental income.
Keywords: I2; J2; J63; 330; teacher mobility; student ability; school choice